Sildenafil or Vardenafil Nonresponders’ Erectile Response to Tadalafil - Ozgur, Berat Cem; Gonenc, Faruk; Yazicioglu, Ahmet H (Urology Journal, 2009)
Introduction: Erectile dysfunction has usually been treated by a phosphodiesterase 5 inhibitor in men, especially in the past decade. Although sildenafil and vardenafil are widely used, there is a high percentage of people who do not respond to these drugs. This study was performed in order to evaluate the efficacy of the lastly presented phosphodiesterase 5 inhibitor, tadalafil, in nonresponder group of patients to sildenafil and vardenafil. Materials and Methods: Forty married men with erectile dysfunction who had taken sildenafil or vardenafil at the maximum recommended doses and had not responded to the treatment were included. They were treated with tadalafil, 20 mg, at least 4 doses at different days. The effectiveness of the treatment was reviewed by different questionnaires, including the International Index of Erectile Function-5 (IIEF-5), Sexual Encounter Profile (SEP) questions 2 and 3, and the Global Assessment Question (GAQ), at the end of the 12th week. Results: The IIEF-5 scores were 11.90 ± 4.78 and 12.67±6.70, before and after at least 4 doses of tadalafil, respectively (P = .30). The rate of positive responses to SEP2, SEP3, and GAQ questions were also insignificantly different after the treatment. During this period, flushing was seen in 10 and headache was seen in 5 patients. Conclusion: The recommended maximum dose for tadalafil insignificantly improved the IIEF5, SEP2, SEP3, and GAQ scores in patients with erectile dysfunction who had not responded to sildenafil and vardenafil. The other treatment alternatives should be in mind after getting no response to the optimum doses and enough trials of sildenafil or vardenafil before trying a tadalafil regimen.